2022
DOI: 10.1128/spectrum.00682-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spartina alterniflora Invasion on Nitrogen Fixation and Phosphorus Solubilization in a Subtropical Marine Mangrove Ecosystem

Abstract: This study revealed the efficient nutrient cycling mechanism of mangroves. Positive coupling effects were observed in sediment quality, NF and PS processes, and NFOPSMs with the invasion of S. alterniflora .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Spartina alterniflora invasion was found to be associated with the simultaneous significant abundance of sulfate reduction genes, sulfur oxidation genes, and polyphosphate kinase ( ppk ) genes, at 25–50 cm depth of mangrove sediment, establishing a strong positive correlation between P and S co-bioconversion, as a unique adaptive trait of avoiding excessive P deposition in marshes causing eutrophication via sulfur metabolism-linked biological P removal ( Mo et al, 2023 ). An obvious metabolic coupling between BNF and P-accumulation/solubilization was observed in S. alterniflora- invaded subtropical mangrove niches in the Beibu Gulf of China ( Zhang et al, 2022 ). One hundred and eight reconstructed genomes associated with N 2 fixation and P-accumulation/solubilization, assigned majorly Gammaproteobacteria and Deltaproteobacteria for this N-P coordinated metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Spartina alterniflora invasion was found to be associated with the simultaneous significant abundance of sulfate reduction genes, sulfur oxidation genes, and polyphosphate kinase ( ppk ) genes, at 25–50 cm depth of mangrove sediment, establishing a strong positive correlation between P and S co-bioconversion, as a unique adaptive trait of avoiding excessive P deposition in marshes causing eutrophication via sulfur metabolism-linked biological P removal ( Mo et al, 2023 ). An obvious metabolic coupling between BNF and P-accumulation/solubilization was observed in S. alterniflora- invaded subtropical mangrove niches in the Beibu Gulf of China ( Zhang et al, 2022 ). One hundred and eight reconstructed genomes associated with N 2 fixation and P-accumulation/solubilization, assigned majorly Gammaproteobacteria and Deltaproteobacteria for this N-P coordinated metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…All strains were cultured in 100 mL Erlenmeyer flasks containing 50 mL LB at 37 °C with continuous rocking on a shaker at 200 rpm for 12 h. Total genomic DNA was extracted using a TIANamp bacterial DNA kit (TIANGEN) according to the instructions of the manufacturer. The quality of the extracted DNA was measured by 1% agarose gel electrophoresis and analyzed using a NanoDrop™ 2000 spectrophotometer [ 5 ] (Thermo Scientific, USA). The amplified products of 16 S rDNA were obtained with specific primers [ 21 ] (Table S1 ) under the following reaction conditions: 95 ℃, 5 min; [95 °C for 30 s; 54 °C for 30 s; and 72 °C for 1 min] × 35 cycles; and 72 °C, 7 min.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it is urgent to find an eco-friendly and economically viable manner to maintain a continuous supply of P in plants. Phosphorus solubilization (PS) is a significant biochemical process in sediments, and plays important roles in alleviating P limitations of mangrove ecosystems [ 5 ]. Several microorganisms can transform insoluble inorganic P into soluble forms available to plants, which are known as phosphate-solubilizing microorganisms (PSMs) [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The similar appearance characteristics ensure the S. alterniflora competitive advantage, while different types of soil nitrogen maintain the overlapping resistance structure of S. alterniflora community. Some studies have found that the nitrogen fixation of S. alterniflora litter is high, which has an activation effect on soil nitrogen fixation organisms, and the high proportion of leaf biomass in S. alterniflora litter is conducive to the nitrogen fixation of S. alterniflora (Zhang et al 2022). The N2O emission rate of S. alterniflora was higher than that of native species, indicating that the S. alterniflora invasion increased the richness of denitrifying bacterial functional groups, and promoted the utilization of NH4 + -N and the accumulation of S. alterniflora biomass (Gao et al 2019;Jin et al 2017).…”
Section: Effects Of Overlapping Resistance Regulated By Different Typ...mentioning
confidence: 99%